PERAN DIDIKAN KELUARGA DALAM MEMBANGUN GENERASI BANGSA YANG BERKARAKTER - wahyuni, Denny (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2019)
If the implementation of the role of parents as natural educators can be carried out well, then the process of forming a nation's generation of character will be more easily realized.